Kebijakan Kampus Inklusif bagi Penyandang Disabilitas (Studi tentang Advokasi Kebijakan Kampus Inklusif di Universitas Brawijaya) - Ulfah Fatmala Rizky (The Center for Disability Studies and Services Brawijaya University, 2015)
This research is done based on the point of view of the researcher in viewing the limited access of college education for students with disabilities. In line to the social model of disability, researcher views that the limited access caused by environment and social system which is not able in accommodating the needs of students with disabilities. As a consequence of the condition, students with disabilities do not have space and chance to actualize themselves. The limited access is also caused by the stereotypes which put them to the social exclusion. Social exclusion can be minimized by applying the concept of inclusivity. The presence of inclusivity concept in the education world gives the new light to the students with disabilities in accessing education. But, this education concept has not applied yet in the college. This research is due to initiate Universitas Brawijaya becomes the pioneer and the model of the first inclusive campus in Indonesia.The method of research used in this research is qualitative method with the action research approach. The focuses of this research are, first, the process of policy advocacy to the inclusive campus to the students with disabilities in Universitas Brawijaya. Second, the policy formulation process of inclusive campus to the students with disabilities. Third, is the effect of inclusive campus to the students with disabilities in Universitas Brawijaya. The location of this research is in Universitas Brawijaya, Malang. The method of collecting data uses observation, interview, and documentation.The conclusions obtained from this research are, first, advocacy done by advocacy team and researcher achieved the expected goal successfully. Second, Universitas Brawijaya accepted the grand design of inclusive campus offered by the advocacy team. Third, Universitas Brawijaya built Center for Disability Studies and Services (CDSS) which was known as the new institution focusing on the services and studies related to the disabilities issues. Fourth, Universitas Brawijaya opened the Special Selection Program to the Students with Disabilities (SSPSD) and serves 20 quotas for students with disabilities.